No evidence of widespread algal bloom intensification in hundreds of lakes. Issue 1 (5th October 2021) - Wilkinson, Grace M; Walter, Jonathan A; Buelo, Cal D; Pace, Michael L
Abstract : Algal blooms, the rapid proliferation of algal biomass often to nuisance or harmful levels, diminish aquatic ecosystem services. Freshwater blooms can cause substantial economic damage by interrupting water supply, limiting recreation, and reducing property values. The interaction between eutrophication and climate change has been hypothesized to drive widespread intensification of blooms in inland waters, although there is little empirical evidence that this trend is pervasive. Here, we show that bloom intensification in inland waterbodies – defined as trends in chlorophyll‐ a of increasing bloom magnitude, severity, or duration – has not been widespread for hundreds of lakes in the US. Only 10.8% of the 323 waterbodies analyzed had significant bloom intensification. Conversely, 16.4% of the waterbodies had significant decreasing trends during the same period. While it is encouraging that bloom intensification is not currently widespread, continued efforts toward aquatic ecosystem protection and restoration are imperative for maintaining ecosystem services into the future.